Foreign Language Teaching Anxiety of Non-Native Pre-Service and In-Service EFL Teachers - Kobul, Mustafa Kerem; Saraçoğlu, İrem Naz (Journal of History Culture and Art Research, 2020)
Despite a robust body of literature on anxiety in language learning, as of yet, teacher’s aspect regarding anxiety seems to have received scant research attention. Apparently, absence of a valid and reliable measuring instrument impeded the empirical research on foreign language teaching anxiety. However, preliminary work well-documents that even teachers get stressed and feel teaching anxiety in their English as a Foreign Language (EFL) classrooms. Thus, the purpose of this study was to investigate the level of foreign language teaching anxiety that non-native pre/in-service EFL teachers experience. The data were collected from 30 in-service and 60 pre-service EFL teachers in two northern cities of Turkey; Trabzon and Yalova. The Foreign Language Teaching Anxiety Scale (FLTAS) was used as the main data collection instrument. No significant difference was found regarding the participants’ gender. When the participants’ scores were compared by the department they were enrolled, it was found that English language teaching department graduate teachers had significantly lower teaching anxiety levels. Significant negative associations between foreign language teaching anxiety and duration of experience as well as graduation department were found. It is believed that the results of the study will be of great contribution to further research into teaching anxiety and have important implications for policymakers of teacher training programs.